Bioacústica de barycholos ternetzi ( Miranda-Ribeiro, 1937) no Brasil Central - Silva, Priscila Lemes de Azevedo (2010)
In most species of anurans, the males vocalizes and through the advertisement call information such as size and physical strength are transmitted in a manner that maintains or increases the relative attractiveness of reproductive females in the household. Thus, males may to engage in competitions acoustic or physical, limiting the acoustic space available for the vocalizations of other males. The goals of this study were to describe the acoustic behavior of Barycholos ternetzi (Miranda-Ribeiro, 1937) study was conducted in October 2009, the National Forest (NF) of Silvânia in the city of Silvânia, the State of Goiás was sampled three environment different in NF: preserved gallery forest, disturbed gallery forest and open area. Males Barycholos ternetzi have wide repertoire, displayed seven distinct vocalizations: advertisement call, aggressive call, three types of fighting call, distress call and mixed call. The advertisement call was the most frequent vocalization. Vocalizations are short and pulsed structure, except for fighting call 1 and distress call, as it had three harmonics. The mixed calls are formed by the emission of two or three notes similar to the advertisement call followed by an aggressive call. The vocalizations were sent to fight in physical combat between two males, while the mixed call was sent in the aggregate at least ten individuals. This suggests that the mixed calls of B. ternetzi could be a graded aggressive call system, which allows male to gradually reduce the number of attractive elements while increasing the aggressiveness of the call. The frequency of the advertisement call was the only acoustic parameter for both the static coefficient of variation for intra and inter. Although, according to the reason CVe /CVi > 1, all parameters are potentially used in individual identification for the advertisement and aggressive calls. The individual discrimination in low density is higher with 41% and 57.5% depending on the call and the acoustic properties of the model. This suggests that there is difference in ranking when compared high and low density for males of B. ternetzi, however, have low individual distinction. For B. ternetzi, the call duration was the most important parameter for the differences between males in the advertisement call. At the aggressive call, dominant frequency was the most important parameter for individuals of B. ternetzi vocalizing in high density, while the call duration to low density. The dominant frequency is influenced by the call duration and the body size, but not by the distance between individuals. B. ternetzi send calls longer and more frequent in low temperature and there is a positive influence on call duration in the repetition rate, indicating that the temporal parameters are more susceptible to fluctuations in temperature while the spectral parameter of the honest old male. Differences in the transmission of the acoustic parameters were seen only between the environments of the disturbed gallery forest and open area, since the reverberation is a common distortion of sound in forests, making the transmission more efficient in the open area.